A Parent-Focused Pilot Intervention to Increase Parent Health Literacy and Healthy Lifestyle Choices for Young Children and Families. (12th May 2013) - Fleary, Sasha; Heffer, Robert W.; McKyer, E. Lisako; Taylor, Aaron
Abstract : Health literacy affects caregivers' ability to engage in preventive health care behaviors for themselves and their children. Studies suggest that health literacy among low-income families needs improvement, and this possibly contributes to disparities in preventive health care rates. Additionally, parents and caregivers may not be able to provide or seek preventive health care for their children because of lack of knowledge and skills to do so effectively. This study designed and piloted an intervention that delivered to parents of young children (1) health literacy information in an experiential manner and (2) practical skills to engage their families in healthy lifestyle choices. Specifically, the intervention focused on diet/nutrition, physical activity, sleep hygiene, parenting, and mental wellness. Postintervention improvements were noted for factual knowledge for diet/nutrition, physical activity, and sleep, beliefs about diet/nutrition, and the relationship between mental health and stress. Additionally, postintervention improvements were noted for general knowledge and beliefs about sleep, knowledge about the relationship between sleep and health, knowledge about common childhood sleep problems, and parents' bedtime interactions with children. The efficacy of the intervention should be evaluated on a larger, more diverse sample in the future with considerations for multiple health behavior change in the evaluation.